Shark aggregation and tourism: opportunities and challenges of an emerging phenomenon. Issue 5 (4th July 2019) - Zemah Shamir, Z.; Zemah Shamir, S.; Tchernov, D.; Scheinin, A.; Becker, N.
ABSTRACT: In the last few winters, shark communities have been aggregating near the Israeli Mediterranean coast, at a specific point, near Hadera power station. This unusual phenomenon has fascinated residents, visitors, kayakers, divers, and swimmers. We analyse the effects of this intense human interest on the sharks, using contingent behaviour, in Hadera and in Ashkelon, where sharks are present and there is available infrastructure for their observation. We also report on changes in shark behaviour due to change in tourism intensity. We find a change of about ILS 4.1 million annually for both sites but a larger individual consumer surplus in Hadera, where sharks are currently observable. Touristic intensity crosses the threshold level by about 12% and making the socio-equilibrium sustainable for both humans and sharks would have a social cost of ILS 0.157 million. This paper, which is based on the assessment of conservation values to marine and coastal tourists, raises a need for spatial planning in order to protect this endangered species.